SISTEM PENILAIAN KINERJA PEGAWAI BERBASIS WEBSITE PADA SDIT BINA INSANI SEMARANG - Febriana Angelia Purba; M. Azis Adnan Sukosugi; Kusnadi Kusnadi (JIEMS (Journal of Industrial Engineering and Management Systems), 2022)
Performance appraisal is a process to determine the quality of human resources in an institution, school, and company. In improving employee performance, SDIT Bina Insani Semarang conducts an assessment of employees as measured by assessment indicators. Employee performance appraisal is carried out by each head of the field with the aim of knowing whether employees have increased or decreased in performance. Based on the problems that exist in SDIT Bina Insani Semarang, which still uses a performance appraisal system with only one side, a system that is able to input performance values from two sides is needed, namely, an assessment system where employees input their own performance values, then the validator will validate. value for its performance. Therefore, the author will build an application that can simplify and assist the school in assessing employee performance, and in completing the writing, the author compiles this report by building an application that uses the PHP Native programming language and MySQL database so that later the results of testing the system carried out on the table questionnaire, the application built successfully runs all features and runs well.